Bioactive Bibenzyl Enantiomers From the Tubers of Bletilla striata - Zhou, Mei; Jiang, Sai; Chen, Changfen; Li, Jinyu; Lou, Huayong; Wang, Mengyun; Liu, Gezhou; Liu, Hanfei; Liu, Ting; Pan, Weidong (Frontiers in Chemistry, 2022)
Six new bibenzyls (three pairs of enantiomers), bletstrins D-F (1-3), were isolated from the ethyl acetate-soluble (EtOAc) extract of tubers of Bletilla striata. Their structures, including absolute configurations were determined by 1D/2D NMR spectroscopy, optical rotation value and experimental electronic circular dichroism (ECD) data analyses, respectively. Compounds 1-3 possess a hydroxyl-substituted chiral center on the aliphatic bibenzyl bridge, which represented the first examples of natural bibenzyl enantiomers from the genus of Bletilla. The antibacterial, anti-tumor necrosis factor (anti-TNF-α) and neuroprotective effects of the isolates have been evaluated. Compounds 3a and 3b were effective against three gram-positive bacteria with minimum inhibitory concentrations (MICs) of 52-105 µg/mL. Compounds 2a and 2b exhibited significant inhibitory effects on TNF-α-mediated cytotoxicity in L929 cells with IC50 values of 25.7 ± 2.3 μM, 21.7 ± 1.7 μM respectively. Subsequently, the possible anti-TNF-α mechanism of 2 was investigated by molecular docking simulation. Furthermore, the neuroprotective activities were tested on H2O2-induced PC12 cells injury model, and compounds 2b, 3a, and 3b (10 μM) could obviously protected the cells with the cell viabilities of 57.86 ± 2.08%, 64.82 ± 2.84%, and 64.11 ± 2.52%, respectively.